2021
DOI: 10.3390/en14123397
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Energy Flexibility of Boats in PV-BESS Based Marina Energy Systems

Abstract: Implementation of alternative energy supply solutions requires the broad involvement of local communities. Hence, smart energy solutions are primarily investigated on a local scale, resulting in integrated community energy systems (ICESs). Within this framework, the distributed generation can be optimally utilised, matching it with the local load via storage and demand response techniques. In this study, the boat demand flexibility in the Ballen marina on Samsø—a medium-sized Danish island—is analysed for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…It has been found that proper BESS charge/discharge planning can ensure system efficiency. Jozwiak et al [18] carried out an analysis of the load demand for boats in Ballen Marina to optimize the cost of energy for sailors and the cost of energy exchanged with the main grid. This proved the important role of demand flexibility analysis as a key element in the energy system.…”
Section: − Literature Reviewmentioning
confidence: 99%
“…It has been found that proper BESS charge/discharge planning can ensure system efficiency. Jozwiak et al [18] carried out an analysis of the load demand for boats in Ballen Marina to optimize the cost of energy for sailors and the cost of energy exchanged with the main grid. This proved the important role of demand flexibility analysis as a key element in the energy system.…”
Section: − Literature Reviewmentioning
confidence: 99%
“…The energy price for EV charging was assumed to be the same for all cars, under the assumption of the hourly varying marina's tariff-developed in [30]. In other words, the marina was assumed to not impose any additional margin on the rental company's electricity price.…”
Section: Modelling Of Electric Car Demandmentioning
confidence: 99%
“…The simulations were carried out for a summer week (15-21 July 2019)-when the marina's load is highest due to the peak tourist season and rental cars are frequently used. The analysis was conducted based on the recorded boat demand of the marina from 2019, presented along with the PV generation data in [30]. The following study cases were taken into consideration: Firstly, the optimal charging strategy was developed, utilising mixed-integer linear programming optimisation.…”
Section: Proposed Optimal Operation Of Marina's Energy Systemmentioning
confidence: 99%
See 2 more Smart Citations